Concept mapping for improving reading comprehension in second language education: a systematic review - Ta, Na; Razali, Abu Bakar (Society for Research and Knowledge Management, 2023)
Reading is an essential learning tool for students to achieve academic and career success, and the ability to read also has a significant impact on students lifelong learning. In the field of ESL/EFL reading teaching, concept mapping has attracted considerable attention as a technique that can be used. To enable researchers and teachers to understand the research focus and application trends of concept mapping in the teaching of ESL/EFL reading, this article provides a literature review of 33 studies published in peer-reviewed journals from 2012 to 2022 on the use of concept mapping in teaching reading comprehension for learners in diverse ESL/EFL contexts. It was found that concept mapping was primarily used and studied among ESL/EFL students at the undergraduate level, serving as an advanced organizer in the pre-reading stage, an instructional medium in the while-reading stage, and a summarizing and evaluation tool in the after-reading stage. It was also found that the application of Kit-Build concept mapping, either in a technology-supported learning environment or with a source connection function, seems to have a promising impact on reading comprehension. Based on these findings, suggestions are provided to ESL/EFL teachers and researchers for better implementation and future research of concept mapping.